Uji Toksisitas Ekstrak Etanolik Batang Tanaman Majapahit (Crescentia cujete) Terhadap Artemia salina Leach - Rahma Diyan Martha; Fatimah (Sistem Informasi, 2020)
Cancer is a disease characterized by uncontrolled cell growth and the ability of these cells to attack biological tissue. Various attempts have been made, one of them with treatment to kill cancer cells, but not a few of these efforts actually cause side effects. This fact demands the need for a safe alternative way to treat cancer using natural ingredients. One of the local natural resources that has the potential to treat cancer is Majapahit (Crescentia cujete). In this study, Majapahit (C. cujete) stem extracts were carried out which have anticancer activity. The first stage was screening by conducting a qualitative analysis of the ethanol extract of the stem of the majapahit plant (C. cujete). Furthermore, a toxicity test was carried out against Artemia salina Leach using the Brine Shrimp Lethality Test (BST) method. Phytochemical testing was carried out to check the content of secondary metabolite compounds contained in the majapahit stem extract, and the results were positive for flavonoids, tannins, saponins and phenolics. This data, supported by spectrophotometric tests, proved that the largest concentration of the ethanolic extract of the majapahit (C. cujete) stem was 24.05% tannin. Then the LC50 test from the toxicity test of the active component of majapahit plant stem extract (C. cujete) against Artemia salina Leach showed a concentration of 0.01 µg / mL and 0.04 µg / mL, namely with a percentage below 50%.